Laparoscopic assisted reduction of jejuno-jejunal intussusception with resection of jejunal polyp in children: A case series - Sanghvi, Beejal V; Parelkar, Sandesh V; Tiwari, Pooja; Shah, Rujuta (Indian Journal of Case Reports, 2019)
Jejunojejunal intussusceptions secondary to polyp as a lead point are extremely rare. Only a few cases have been reported in the English literature. Here, we report the case series of two such cases who presented to us as irreducible intussusceptions and were managed successfully by laparoscopic-assisted transumbilical reduction and resection. Thus laparoscopic-assisted management of this rare presentation is feasible even in smaller children.